An Experimental Study on the Use of Calcium Alginate to Heal Colonic Anastomoses. (2nd January 2016) - de la Portilla, F.; García-Cabrera, A. M.; Pereira, S.; de Marco, F.; Molero, M.; Muntane, J.; Padillo, F. J.
ABSTRACT: Background: Anastomotic leak is considered the major complication following abdominal surgery. In recent years, the use of a variety of sealing materials for the prevention of leaks has been analyzed. Different biomaterials have been employed as scaffolds to favour tissue repair and regeneration. Among these materials we must mention alginate, a natural polymer with different applications as temporary supporting matrix. The aim of the present study is to evaluate the behavior of both alginate-impregnated sutures and lyophilized alginate sponges in the healing process of colonic anastomes using an experimental animal model.Material and methods: A preliminary study was undertaken to select the adequate scaffold. Animals (n = 45) were distributed into three groups: control (colonic anastomosis using non-continuous 5-0 Polyglactin 910 suture), suture (colonic anastomosis using suture impregnated with alginate gel at 4%) and sponge (colonic anastomosis using suture reinforced with lyophilized alginate sponge). The macroscopic and histological variables were assessed at 4, 8 and 12 days after surgical intervention.Results: No statistically significant differences have been observed between the groups during the analysis of macroscopic variables. Animals with sponge implantation showed a greater degree of epithelial reepithalization, less acute and chronic inflammation and greater collagen deposit.Conclusions: The use of lyophilized alginate sponges to reinforce colonic anastomoses in an animal model reduces inflammation and promotes the earlier formation of greater collagen deposits without increasing the number of adhesions or the incidence of stenosis.